Naturally occurring systemic canine distemper virus infection in a pup - Headley, Selwyn A.; Sukura, Antti (Brazilian Journal of Veterinary Pathology, 2009)
This report describes the pathologic and immunohistochemical findings associated with naturally occurring systemic canine distemper virus (CDV) infection in a dog. Clinically, there was lymphopenia and hyperkeratosis of footpads, while pneumonia was identified by radiology. Gross lesions consisted of bilateral ocular discharge and discrete digital hyperkeratosis. By histopathology, there was severe interstitial pneumonia and necrosis of splenic germinal centers. Additionally, eosinophilic intranuclear inclusion bodies were observed within cerebellar astrocytes without marked manifestation of CDV-induced encephalitis. Further, intracytoplasmic bodies were identified within the epithelial cells of the renal pelvis, lung, and urinary bladder. Immunohistochemistry identified the presence of CDV antigens in these tissues and further confirmed the systemic infection to the epidermis of footpads, heart, liver, intestine, spleen, and lymph node.